"Are we forgetting the smallest, sub 10 nm combustion generated particles?". Issue 1 (December 2015) - Pedata, Paola; Stoeger, Tobias; Zimmermann, Ralf; Peters, Annette; Oberdörster, Günter; D'Anna, Andrea
Abstract Although mass emissions of combustion-generated particulate matter have been substantially reduced by new combustion technology, there is still a great concern about the emissions of huge numbers of sub-10 nm particles with insignificant mass. These particles have up to orders of magnitude higher surface area to mass ratios compared to larger particles, have surfaces covered with adsorbed volatile and semi-volatile organic species or even are constituted by such species. Currently there is only very little information available on exposure and related health effects specific for smaller particles and first evidences for long-term health effects has only been recently published. However, the fact that these nanoparticles are not easily measured at the exhausts and in the atmosphere and that their biological activity is obscure does not mean that we can overlook them. There is an urgent need to develop i) reliable methods to measure sub-10 nm particles at the exhaust and in the atmosphere and ii) a robust correlation between the chemical structure of the molecules making up combustion-generated nanoparticles and health burden of new combustion technologies. Our attention has to turn to this new class of combustion-generated nanoparticles, which might be the future major constituents of air pollution.